Communicative Strategies in Medical Discourse: Problems in Doctor–Patient Interaction - Burxonova, Mohira (The Lingua Spectrum, 2025)
In contemporary medical practice, communication between physicians and patients transcends the mere exchange of information; it constitutes a socio-psychological interaction grounded in mutual trust, cooperation, and respect. Effective communication within medical discourse exerts a direct influence on patients’ comprehension of their illnesses, their positive orientation toward treatment, and the overall acceleration of recovery. The physician’s tone of speech, lexical choices, politeness, and precision serve as determinants of the patient’s emotional state and adherence to medical recommendations. The success of medical communication is largely contingent upon the appropriate selection of linguistic means. When explanations are rendered in ambiguous, overly complex, or excessively technical language, patients often experience confusion and uncertainty. Conversely, linguistic clarity facilitates mutual understanding, eases interaction, and reinforces trust. The present study is directed toward examining the interrelationship among language, politeness, clarity, and cultural factors within medical communication. It further seeks to identify linguistic and pragmatic mechanisms that contribute to enhancing the effectiveness of doctor-patient interaction. As the research aims to analyze specific challenges within medical discourse through a linguistic prism and to propose viable solutions, issues pertaining to medical ethics are also addressed as an integral component of the investigation. By analyzing linguistic strategies and their social effects, the research emphasizes the necessity of training medical professionals in patient-centered communication to ensure both psychological comfort and high-quality care.